Numerical simulation of creep notched bar of P91 steel (Fracture and Structural Integrity, 2022)
Numerous components designed for use at elevated temperatures now exhibit multiaxial stress states as a result of geometric modification and material inhomogeneity. It is necessary to anticipate the creep rupture life of such components when subjected to multiaxial load. In this work finite element analysis has been performed to study the influence of different notches, namely blunt and medium notches on the stress distribution across the notch throat during the creep exposure. Within the FE model, a ductility exhaustion model based on the Cocks and Ashby model was utilized to forecast the creep rupture time of notched bar P91 material. The lower and upper bound of creep ductility are employed in the FE analysis. Different notch specimens have different stress and damage distribution. It is shown that for both types of notches, the von Mises stress is lower than the net stress, indicating the notch strengthening effect. The accumulation of creep damage in the minimum cross-section at each element across the notch throat increases over time. The point at which damage first occurs is closer to the notch root for the medium notch than for the blunt notch. The long-term rupture life predicted for blunt notch specimens appears to be comparable to that of uniaxial specimens. The upper bound creep ductility better predicts the rupture life for medium notches.
Keywords: P91 steel; Mutiaxial stress state; Finite element analysis; Ductility exhaustion model; Cocks and Asbhy model